Brainwave Signals of Language Learning Anxiety: A systematic review of EEG studies and Its Contributions to ELT - I Ketut Wardana (SPHOTA: Jurnal Linguistik dan Sastra, 2026)
Language learning anxiety poses a significant challenge for English Language Teaching (ELT) in Indonesian education; however, traditional methods frequently neglect its neurophysiological foundations. Therefore, it is imperative to investigate learning anxiety through EEG-based brainwave monitoring. This review study examines how EEG assessments identify specific brainwave types, brain regions, and treatments for learning anxiety. A systematic literature review (SLR) approach adhered to PRISMA guidelines. The flow diagram results indicate that out of 250 articles identified from Scopus-indexed journals, 140 passed the initial screening stage, 90 were selected for further review, and only 30 met the inclusion criteria. These articles were categorized into three main themes: brainwave types, brain regions, and EEG treatment for anxiety. The findings indicated that EEG studies consistently and accurately detect learning anxiety through increased beta wave activity and decreased alpha and theta wave activity, particularly in the prefrontal cortex, which is linked to cognitive stress and emotional regulation dysfunction. Additionally, significant brain activation was observed in the frontal, prefrontal, parietal, and temporal regions, as well as in the limbic system. EEG-based interventions, such as neurofeedback and vagus nerve stimulation, were also found to be effective in reducing anxiety through non-pharmacological means. However, current research is still limited to experimental studies conducted in laboratory settings, which do not fully capture the dynamic nature of learning anxiety in real classroom contexts for better input of teaching strategies. The study implies that English language teaching should incorporate neuroscience-informed, anxiety-reducing strategies, providing practical insights for teachers to adapt instructional techniques and improve learning outcomes.